Glycosylation enhances peptide hydrophobic collapse by impairing solvation - Cheng, Shanmei; Edwards, Scott A.; Jiang, Yindi; Gräter, Frauke (ChemPhysChem, 2010)
Post-translational N-glycosylation of proteins is ubiquitous in eukaryotic cells, and has been shown to influence the thermodynamics of protein collapse and folding. However, the mechanism for this influence is not well understood. All-atom molecular dynamics simulations are carried out to study the collapse of a peptide linked to a single N-glycan. The glycan is shown to perturb the local water hydrogen-bonding network, rendering it less able to solvate the peptide and thus enhancing the hydrophobic contribution to the free energy of collapse. The enhancement of the hydrophobic collapse compensates for the weakened entropic coiling due to the bulky glycan chain and leads to a stronger burial of hydrophobic surface, presumably enhancing folding. This conclusion is reinforced by comparison with coarse-grained simulations, which contain no explicit solvent and correspondingly exhibit no significant thermodynamic changes on glycosylation.
Gesehen am 08.03.2023